Governance instruments and liquid wastes management in urban industrial areas of Tanzania: a case of Morogoro textile industry - Mwakaboko, Humphrey Donald (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University